Transitioning from civil war to government: leadership in post-conflict reconstruction in South Sudan and Mozambique - Gatehouse, Clare Annabel (My University, 2017)
This study examines leadership and statebuilding in the very specific context of the transition of a rebel group to a governing entity of a post-conflict state by comparing the cases of Mozambique and South Sudan. Drawing on theories of political leadership, statebuilding and post-conflict reconstruction, and recent studies on political legitimacy, this study provides insight into the processes by which leaders interact with and build the institutions of state that both enable their governance and that may ultimately constrain their authority, and the impact of external actors on these processes. This study focuses particularly on the critical interaction between political leaders and the institution of the rebel group turned political party that they lead in the fragile post-conflict period. This study traces how FRELIMO in Mozambique and the SPLM in South Sudan built sufficient political legitimacy in order to be considered the natural party of governance upon independence in each country. It also compares how RENAMO in Mozambique sought to make the transition from rebels to politicians. It then closely examines how leaders’ and parties’ political legitimacy was built or lost in subsequent years and the impact of this on building the critical institutions of state and ultimately on the stability of that state. Both cases highlight, for different reasons, that leaders matter particularly when institutions are weak. This report contends that a critical causal mechanism in a successful transition from fighting a war to governing a country is establishing and maintaining legitimacy – both internally with the governed population and externally with key international partners. How leaders balance internally derived and externally derived legitimacy often proves to be important. External actors are often fundamental in bestowing legitimacy on armed groups, even when there are other groups claiming to represent the interests of the population. While externally derived legitimacy is important in getting these parties into power, sources of internal legitimacy, derived from their own populations by parties and leaders, are critical in shaping their ability to offer stable government. Each case demonstrates that legitimacy must be maintained in order to maintain stability.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Arts, June 2017
Keywords: Political leadership--South Sudan; Political leadership--Mozambique; Leadership--South Sudan; Leadership--Mozambique; Public administration--South Sudan; Public administration--Mozambique